Analisis Laporan Keuangan PT Garuda Indonesia Menggunakan Metode Horizontal dan Vertikal untuk Menilai Kinerja Keuangan - Sharon Victoria Chendra; Eugenia Laeticia; Keisya Alayah Putri; Dyah Cahyasari (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
This study assesses the financial performance of PT Garuda Indonesia from 2021 to 2023 through a quantitative analysis of its published financial statements during this period. The study, conducted using quantitative methods, examined all published financial statements of PT Garuda Indonesia within this timeframe. Specifically using vertical and horizontal analytic methods in analyzing the financial health of the company. By analyzing the company’s published financial statements, the study aims to provide insights into its financial health. Despite starting with a negative equity position, PT Garuda Indonesia displayed remarkable financial improvements, particularly in 2022 and 2023. The company successfully increased its net profit, streamlined asset utilization, and achieved a substantial reduction in liabilities. However, certain accounts, such as trade debt, showed fluctuations throughout the analyzed period, reflecting the challenges of navigating the dynamic aviation industry. Despite these variations, the overall trend indicates sound financial management and resilience in adapting to an ever-changing market environment. These findings highlight PT Garuda Indonesia's commitment to financial recovery and sustainable growth, demonstrating its ability to overcome adversity and strengthen its position within the competitive aviation sector.